Mathematical connections promoted in telebachillerato textbooks about slope concept - Cruz Acevedo, Alan Andrés; García-García, Javier (IE Revista de Investigación Educativa de la REDIECH, 2023)
The aim of this research was to identify the mathematical connections promoted in four Mexican telebachillerato school textbooks when exploring different conceptualizations of slope. To achieve this, a conceptual framework was adapted to define the concept of mathematical connections and the different conceptualizations of slope. Content analysis was employed to analyze the textbooks. Based on the lesson presentations in these materials, the mathematical connections were categorized as either implicit or explicit. The findings revealed a total of 160 explicit and 202 implicit mathematical connections, underscoring the vital role that teachers must play in instructing students on how to utilize these connections in the Mexican telebachillerato classroom, since mathematical connections are promoted wihin the textbooks but they are implicit in some instances. The results indicated that the four textbooks analyzed promote the following mathematical connections: procedural, different representations, meaning, feature, part-whole, inter-conceptual, modeling, and implication.